2014
DOI: 10.12659/ajcr.891007
|View full text |Cite
|
Sign up to set email alerts
|

Management of Spindle Cell Carcinoma of the Maxillary Sinus: A Case Report and Literature Review

Abstract: Patient: Male, 52Final Diagnosis: Spindle-cell carcinoma of the maxillary sinusSymptoms: —Medication:—Clinical Procedure: Functional endoscopic sinus surgery • total maxillectomySpecialty: OtolaryngologyObjective:Rare diseaseBackground:Carcinosarcomas, also known as spindle cell carcinomas, are rare and highly aggressive tumors characterized by dual histologic differentiation of squamous cell and mesenchymal cell tumors. Occurrence of carcinosarcoma in maxillary sinus is very rare, with only 11 cases reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…This explanation has been supported by ultrastructural and histpathologic examinations (9, 10). Nappi et al (11) There is a controversy about the management of spindle cell carcinoma due to the scarcity, difficulty of histological confirmation, and a shortage of literature about disease pathogenesis, outcome survey, and management guidelines (1,3,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explanation has been supported by ultrastructural and histpathologic examinations (9, 10). Nappi et al (11) There is a controversy about the management of spindle cell carcinoma due to the scarcity, difficulty of histological confirmation, and a shortage of literature about disease pathogenesis, outcome survey, and management guidelines (1,3,12).…”
Section: Discussionmentioning
confidence: 99%
“…Either radiotherapy or chemotherapy is an alternative option for inoperable patients or those with sinonasal tumors. Overall, the time of diagnosis and the site of lesion affect the outcome so that early stage diagnosis and extraoral lesion have been resulted in better outcomes (12)(13)(14)). Some studies reported the increased mortality rate in the tumors of the head and neck area as a result of lower resistance to tumor-spreading along tissue planes and extensive lymph drainage system with resultant lymphatic and distant metastases (3,4,13).…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant radiation and/or chemotherapy should be used in case of incomplete removal or positive surgical margins [12]. While other studies suggest that postoperative chemoradiation therapy improves patient prognosis and should be considered as the standard therapeutic modality [13].…”
Section: Carcinosarcomasmentioning
confidence: 99%
“…Despite its rarity in the head and neck region, the most frequently involved site is the larynx, with reports of cases found in nasal cavity, hypopharynx, oral cavity, esophagus, trachea, maxilla and skin also present in the literature [6]. Spindle cell carcinoma arising in maxilla is much rarer occurrence in literature [7] with few cases reported since 1957 (Table 1).…”
Section: Introductionmentioning
confidence: 99%